MENYIAPKAN GENERASI BERWAWASAN GLOBAL DENGAN PELATIHAN BAHASA INGRIS KEPADA ANAK USIA SEKOLAH DASAR - Poniman; Muhammad Sirod (LPPM ITB AAS Indonesia Surakarta, 2026)
Abstract This community service program aims to assist the residents of Karangasem Village, Laweyan, Surakarta. Parents in Karangasem who have elementary school-aged children feel the need to enhance their children's English skills. The D3 English Study Program collaborates with Karangasem Village to help them by conducting English training for elementary school-aged children entitled